A GSK3-SRF Axis Mediates Angiotensin II Induced Endothelin Transcription in Vascular Endothelial Cells - Yang, Yuyu; Wang, Huidi; Zhao, Hongwei; Miao, Xiulian; Guo, Yan; Zhuo, Lili; Xu, Yong (Frontiers in Cell and Developmental Biology, 2021)
Endothelin, encoded by ET1, is a vasoactive substance primarily synthesis in vascular endothelial cells (VECs). Elevation of endothelin levels, due to transcriptional hyperactivation, has been observed in a host of cardiovascular diseases. We have previously shown that serum response factor (SRF) is a regulator of ET1 transcription in VECs. Here we report that angiotensin II (Ang II) induced ET1 transcription paralleled activation of glycogen synthase kinase 3 (GSK3) in cultured VECs. GSK3 knockdown or pharmaceutical inhibition attenuated Ang II induced endothelin expression. Of interest, the effect of GSK3 on endothelin transcription relied on the conserved SRF motif within the ET1 promoter. Further analysis revealed that GSK3 interacted with and phosphorylated SRF at serine 224. Phosphorylation of SRF by GSK3 did not influence its recruitment to the ET1 promoter. Instead, GSK3-mediated SRF phosphorylation potentiated its interaction with MRTF-A, a key co-factor for SRF, which helped recruit the chromatin remodeling protein BRG1 to the ET1 promoter resulting in augmented histone H3 acetylation/H3K4 trimethylation. Consistently, over-expression of a constitutively active GSK enhanced Ang II-induced ET1 transcription and knockdown of either MRTF-A or BRG1 abrogated the enhancement of ET1 transcription. In conclusion, our data highlight a previously unrecognized mechanism that contributes to the transcriptional regulation of endothelin. Targeting this GSK3-SRF axis may yield novel approaches in the intervention of cardiovascular diseases.